Early Music Printing in German-Speaking Lands - Lindmayr-Brandl, Andrea; Giselbrecht, Elisabeth; McDonald, Grantley (Taylor & Francis, 2018)
The first century of music printing in Germany had its own internal dynamics, affected by political and social events such as the Reformation. Yet it also had an international dimension: German printers set up shops all around Europe, taking materials and techniques with them, or exporting necessary materials such as type. For the first time, this collection brings together the different strands that define the German music printing landscape from the late fifteenth to the late sixteenth century. From the earliest developments in music printing and publishing, to printing techniques and solutions, the commerce of music printing, and intellectual history, the chapters outline broad trends in the production of different genres of printed books and examine the work of individual printers. The book draws upon the rich information gathered for the online database Catalogue of early German printed music / Verzeichnis deutscher Musikfruhdrucke (vdm), the first systematic descriptive catalogue of music printed in the German-speaking lands between c. 1470 and 1540, allowing precise conclusions about the material production of these printed musical sources. The result is a highly original and varied picture of the beginnings of music printing in a geographical region that, until now, has been somewhat neglected.